The tadpole of Odontophrynus cordobae Martino & Sinsch, 2002 (Anura: Cycloramphidae) from central Argentina - Grenat, Pablo R.; Zavala Gallo, Lucio M.; Salas, Nancy E.; Martino, Adolfo L. (Zootaxa, 2009)
The genus Odontophrynus is endemic to South America and currently consists of 10 recognized species distributed in southern and eastern of the continent (Rosset et al. 2006; Rosset 2008; Amaro et al. 2009). The americanus group is currently represented by four species: O. americanus, O. lavillai, O. cordobae and O. maisuma. Odontophrynus cordobae is cryptic with their polyploid counterpart O. americanus and inhabited in the center and northwestern Córdoba and south of Santiago del Estero provinces (Martino and Sinsch 2002; Rosset et al. 2006). The tadpole of O. cordobae remains undescribed. Herein we describe the larval external morphology and oral disc.